Addressing priority questions of conservation science with palaeontological data - Kiessling, W; Raja, N; Roden, V; Turvey, S; Saupe, E (Royal Society, 2019)
Palaeontologists often ask identical questions to those asked by ecologists. Despite this, ecology is considered a core discipline of conservation biology, while palaeontologists are rarely consulted in the protection of species, habitats and ecosystems. The recent emergence of conservation palaeobiology presents a big step towards better integration of palaeontology in conservation science, although its focus on historical baselines may not fully capture the potential contributions of geohistorical data to conservation science. In this essay we address previously defined priority questions in conservation and consider which of these questions may be answerable using palaeontological data. Using a statistical assessment of surveys, we find that conservation biologists and younger scientists have a more optimistic view of potential palaeontological contributions to the field compared to experienced palaeontologists. Participants considered questions related to climate change and marine ecosystems to be the best addressable with palaeontological data. As these categories are also deemed most relevant by ecologists and receive the greatest research effort in conservation, they are the natural choice for future academic collaboration.